147 'CHAMPIONING CONTINENCE'—ESTABLISHMENT OF A MULTIDISCIPLINARY CONTINENCE PROMOTION WORKING GROUP IN AN ACUTE TEACHING HOSPITAL. (18th November 2021) - Howard, M; Peppard, S; O'Dwyer, E; McLoughlin, K; McLoughlin, L; Carolan, N; Walsh, N; Chukwureh, W; Russell, E; Wilson, L; Kottackal, L M; Kelly, M; et al.
Abstract: Background: In line with the National Frailty Programme 1, patients over the age of 75 admitted to hospital should have a comprehensive geriatric assessment including the assessment of current continence status and any history of incontinence. Up to 39% of adults are reported to develop new onset urinary incontinence during admission to hospital 2, 3, however studies show that is it a problem not always identified by staff members, 4 . In response to these observations within an acute teaching hospital, a continence working party was formed involving members of nursing, physiotherapy and occupational therapy colleagues to explore the current practice and culture relating to continence management. Methods: The group established key objectives which were broken into four strands; 1. Audit of documentation of baseline continence on admission (therapy and nursing). 2. Obtaining access to additional types of continence wear. 3. Staff education. 4. Pre and post education survey. Results: 1. Audit of documentation demonstrated poor standards of documentation of baseline continence. This led to an amendment to questioning prompts on therapy initial assessment forms and a plan to further evaluate the nursing documentation. 2. A wider array of continence wear has been made available on the wards providing greater options for patients. 3. Staff education session was compiled by a specialist physiotherapist and is widely available for staff to access on the hospitals online training portal. 4. Pre-education surveys have been completed with a view to re-administering following education roll-out. Conclusion: The aim of this multidisciplinary working group is to equip staff with the correct resources, knowledge, and confidence to ensure best practice promotion of continence on the targeted wards. This project is the first strand of a wider culture changed that is needed around continence promotion for older adults in the acute setting.